How Often? Towards an Optimum Survey Interval for Mobile Seabeds - Kember, I. D. (The International Hydrographic Review, 2015)
This paper offers practical guidelines for any review of survey periodicity for offshore locations. Beginning with a review of the data sources which the hydrographic surveyor is likely to have to hand, the paper proceeds to an extended example (South Sand Head). Turning from the particular to the general, a two-stage operation is suggested for any offshore area : (а) Investigation, using an historical series of hydrographic surveys as primary source, into changes occurring in the past — particularly during the recent past. Changes should be described in quantitative terms wherever possible. (б) An attempt should be made to understand the sedimentary mechanism causing the changes noted in (a) above. When both stages have been completed, the investigator will be ready to make his decision. Throughout, methods of graphical analysis are suggested.